Pengaruh Co-Branding, Celebrity Worship, dan Packaging Design terhadap Keputusan Pembelian Shampoo CLEAR TinyTAN - Dheajeng Novida Naila Rochmatin; Rizky Dermawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Consumers prefer other brands of anti-dandruff shampoo products than the CLEAR brand. Therefore, CLEAR requires a new strategy to improve consumer purchase decisions. The purpose of this study was to determine the effect of co-branding, celebrity worship, and packaging design on purchase decisions for CLEAR TinyTAN shampoo. The population in this study were fans of BTS (ARMY) in Surabaya and had purchased CLEAR TinyTAN shampoo. Samples were taken using nonprobability sampling with purposive sampling. Determination of the sample with the Lemeshow formula and produce as many as 100 respondents with the age criteria of 18-39 years. Data collection techniques used primary data sourced from questionnaires and secondary data from literature studies. Data analysis techniques in the form of SEM-PLS. The results of the test conclude that co-branding and packaging design have a substantial effect, while celebrity worship has a non-substantial effect on the purchase decision of CLEAR TinyTAN shampoo.